Recording our truth: Using home, housing and homelands to understand Nishnawbe Aski Nation’s housing emergency - Herskovits, Jeffrey; Kaupp, Courtney; McKay, Michael; McCartney, Shelagh; Dextrase, Hillary (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2026)
Planning in the context of a housing emergency by both public and private sector professionals often adopts a forward-focused approach, obscuring the context that created the emergency and ignoring the perspectives of those who have experienced the emergency first-hand. This article discusses the research project, Recording Our Truth, which engaged Elders from Nishnawbe Aski Nation (NAN) territory in their lived experience of the housing emergency that is ongoing in the territory. The project sought to understand: how did the current housing emergency begin? And could learning about its beginning lead toward solutions? Answers to these questions were sought through interviews and mapping with Elders who had experienced the emergency over their lifetimes, leading to nuanced insights on how experiences of home, housing, and homeland have been shaped by violent colonial histories, and lessons for the future of addressing the housing emergency in NAN territory.